2011
DOI: 10.1016/j.cub.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Differential Prefrontal White Matter Development in Chimpanzees and Humans

Abstract: A comparison of developmental patterns of white matter (WM) within the prefrontal region between humans and nonhuman primates is key to understanding human brain evolution. WM mediates complex cognitive processes and has reciprocal connections with posterior processing regions [1, 2]. Although the developmental pattern of prefrontal WM in macaques differs markedly from that in humans [3], this has not been explored in our closest evolutionary relative, the chimpanzee. The present longitudinal study of magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 47 publications
(102 reference statements)
0
46
0
1
Order By: Relevance
“…One commonly held view of self-regulation is that humans have evolved specific control systems, particularly within the prefrontal cortex (PFC), that permit superior planning and behavioral flexibility, perhaps owing to the disproportionate amount of cortical expansion in the human PFC (Rilling 2006), increased white-matter PFC connectivity (Schoenemann et al 2005), or an extended period of prefrontal white-matter development relative to nonhuman primates (Sakai et al 2011). As human safety and survival has long depended on living in groups, investigators have suggested that humans have a fundamental need to belong (Baumeister & Leary 1995) that motivates them to avoid behaviors that could lead to their expulsion from the group (e.g., theft of common resources), as this would greatly lessen their chances for survival (Goodall 1986, Heatherton 2011).…”
Section: Where Is Self-regulation In the Brain?mentioning
confidence: 99%
“…One commonly held view of self-regulation is that humans have evolved specific control systems, particularly within the prefrontal cortex (PFC), that permit superior planning and behavioral flexibility, perhaps owing to the disproportionate amount of cortical expansion in the human PFC (Rilling 2006), increased white-matter PFC connectivity (Schoenemann et al 2005), or an extended period of prefrontal white-matter development relative to nonhuman primates (Sakai et al 2011). As human safety and survival has long depended on living in groups, investigators have suggested that humans have a fundamental need to belong (Baumeister & Leary 1995) that motivates them to avoid behaviors that could lead to their expulsion from the group (e.g., theft of common resources), as this would greatly lessen their chances for survival (Goodall 1986, Heatherton 2011).…”
Section: Where Is Self-regulation In the Brain?mentioning
confidence: 99%
“…While no studies have focused on synaptogenesis in the marmoset prefrontal cortex, studies on the primary visual cortex suggest that a doubling of the volume of this area takes place between birth and 3 months of age, characterized by the same 'overshoot' in growth that is followed by reduction (Missler et al 1993). A recent study using longitudinal magnetic resonance imaging scans of three chimpanzees between 6 months and 6 years of age, in comparison with humans and rhesus macaques, showed that the proportion of white matter in the chimpanzee prefrontal cortex increases at a slower rate than in humans (Sakai et al 2011). These results provide further support for the suggestion that the maximum increase in prefrontal white matter takes place slightly earlier in chimpanzees than in humans.…”
Section: Evolution Of Adrenarchementioning
confidence: 99%
“…Among anthropoid primates, the human brain is characterized by the highest proportional volume (35%) of white matter formed by long-range axons that underlie the grey matter with its local networks of neurons wired by dendrites and mostly non-myelinated axons [33]. Both chimpanzees and humans differ from macaques ( presumed to represent the ancestral primate pattern) in the maturation of the brain's prefrontal portion [34]: white-matter volume increases from infancy to adulthood in chimpanzees as well as humans, but not in macaques. However, during infancy, prefrontal white-matter volume increases at a higher rate in humans than in chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…However, during infancy, prefrontal white-matter volume increases at a higher rate in humans than in chimpanzees. Sakai et al [34,35] suggested that the protracted development enhances the impact of postnatal experiences on neural connectivity and that 'the rapid development of the human prefrontal white matter during infancy may help the development of complex social interactions'.…”
Section: Introductionmentioning
confidence: 99%